AN ANALYSIS OF PROFESSOR LOURENS DU PLESSIS’ EARLY (PRO-LIFE) AND LATER (PRO- CHOICE) PERSPECTIVES ON ABORTION - Najma Moosa (Obiter, 2016)
Abortion, or termination of pregnancy, albeit in gradations from most to less restrictive to unrestricted, has always been legally allowed in South Africa. This questions the need for the introduction of new law. Legalisation of abortion has reduced abortion to a form of failed contraception. Illegal abortions motivated new law, as well as research, Professor Lourens Marthinus du Plessis’ constitutional argument favouring women’s (reproductive) right to abortion. Yet, illegal abortions continue as before democracy when the seemingly Christian, racially-motivated law, was flouted by white and black women alike. The Constitution adopts a neutral position on the right to life, but is decidedly pro-abortion. This does not imply that a constitutional challenge, which has yet to occur, seeking to amend the current status quo and to provide protection to an unborn, may be an exercise in futility. This article is written in honour of, and analyses the role and early “pro-life” views of the now retired Du Plessis as a white Afrikaner male, husband, father and proud grandfather, schooled in a traditional, conservative strand of Christianity, and as an anti-apartheid constitutional lawyer and drafter – to determine whether his liberal political views are compatible with his moral views and whether they may have since changed.